2016
DOI: 10.1002/mnfr.201500900
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic risk and gut microbial phytoestrogen metabolite phenotypes

Abstract: Recent evidence supports that the gut microbial community, independently and/or interactively with dietary intake, is a target for reducing cardiovascular disease risk through its effects on cardiometabolic risk factors. Dietary phytoestrogens may be a source for interactive effects. Phytoestrogens, such as isoflavones, lignans, and flavonoids, are compounds found in plants that have estrogenic or antiestrogenic activities, as well as antioxidant, antiproliferative, or apoptotic actions. Given these physiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
65
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 123 publications
(170 reference statements)
0
65
0
Order By: Relevance
“…Although the concept of metabotype is quite broad and different criteria have been described in the literature for its definition, the term ‘gut microbiota polyphenol metabotype’ refers to a metabolic phenotype characterized by specific polyphenol‐derived metabolites produced by a specific microbial ecology. Overall, this is not a quantitative but a qualitative criterion, (i.e., producer vs non‐producer), it is less influenced by external factors and mainly characterize individuals that harbor particular microbial ecologies . In this context, the stratification of individuals according to their gut microbiota polyphenol metabotypes has been proposed to understand individuals’ response to dietary polyphenols, which is crucial in the context of personalized nutrition …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the concept of metabotype is quite broad and different criteria have been described in the literature for its definition, the term ‘gut microbiota polyphenol metabotype’ refers to a metabolic phenotype characterized by specific polyphenol‐derived metabolites produced by a specific microbial ecology. Overall, this is not a quantitative but a qualitative criterion, (i.e., producer vs non‐producer), it is less influenced by external factors and mainly characterize individuals that harbor particular microbial ecologies . In this context, the stratification of individuals according to their gut microbiota polyphenol metabotypes has been proposed to understand individuals’ response to dietary polyphenols, which is crucial in the context of personalized nutrition …”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, the distribution of urolithin metabotypes in the population has been reported to be mainly determined by aging . Regarding isoflavones, two metabotypes have been identified based on the excretion of the microbial metabolite equol, i.e., equol‐producers and non‐producers, although a third potential metabotype is currently being considered regarding those individuals that are not able to produce the metabolite O ‐desmethylangolensin (ODMA) . Therefore, i) polyphenol gut metabotypes are based on a binary response (presence vs absence of metabolites), ii) their possible confirmation requires the analysis of large cohorts, and iii) the inclusion of a number of potential variables such as age is mandatory in the multivariate analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Birru et al . ; Frankenfeld ). The definition of the equol producer phenotype is currently based on urinary or serum equol concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…By doing so, a number of human randomized controlled trials found beneficial effects of soy intake in equol-producing subjects but not in nonproducers. Those effects include improvement of risk factors for breast cancer, prostate cancer, cardiovascular disease and alleviation of osteoporosis (Shor et al 2012;Birru et al 2016;Frankenfeld 2017). The definition of the equol producer phenotype is currently based on urinary or serum equol concentrations.…”
Section: Introductionmentioning
confidence: 99%